Microstructure and Mechanical Properties of Novel High-Strength, Low-Activation Wx(TaVZr)100−x (x = 5, 10, 15, 20, 25) Refractory High Entropy Alloys - Jingsai Zhang; Shunhua Chen; Jiaqin Liu; Zhenhua Qing; Yucheng Wu (Entropy, 2022)
In this work, novel high-strength, low-activation Wx(TaVZr)100−x (x = 5, 10, 15, 20, 25) refractory high entropy alloys (RHEAs) were prepared by vacuum arc melting. Their microstructure, compressive mechanical properties, hardness, and fracture morphology were investigated and analyzed. The results show that the RHEAs possess a disordered BCC phase, ordered Laves phase, and Zr-rich HCP phase. Their dendrite structures were observed, and the distribution of dendrites became gradually more dense with an increase in W content. The RHEAs demonstrate high strength and hardness, with these properties being higher than in most reported tungsten-containing RHEAs. For example, the typical W20(TaVZr)80 RHEA has a yield strength of 1985 MPa and a hardness of 636 HV, respectively. The improvement in terms of strength and hardness are mainly due to solid solution strengthening and the increase in dendritic regions. During compression, with the increase in the applied load, the fracture behavior of RHEAs changed from initial intergranular fractures to a mixed mode combining both intergranular and transgranular fractures.